Manganese superoxide dismutase and glutathione peroxidase-1 contribute to the rise and fall of mitochondrial reactive oxygen species which drive oncogenesis() - Ekoue, Dede N. (Biochim Biophys Acta, 2017)
Reactive oxygen species (ROS) largely originating in the mitochondria play essential roles in the metabolic and (epi)genetic reprogramming of cancer cell evolution towards more aggressive phenotypes. Recent studies have indicated that the activity of superoxide dismutase (SOD2) may promote tumor progression by serving as a source of hydrogen peroxide (H(2)O(2)). H(2)O(2) is a form of ROS that is particularly active as a redox agent affecting cell signaling due to its ability to freely diffuse out of the mitochondria and alter redox active amino acid residues on regulatory proteins. Therefore, there is likely a dichotomy whereas SOD2 can be considered a protective anti-oxidant, as well as a pro-oxidant during cancer progression, with these effects depending on the accumulation and detoxification of H(2)O(2). Glutathione peroxidase-1 GPX1, is a selenium-dependent scavenger of H(2)O(2) which partitions between the mitochondria and the cytosol. Epidemiologic studies indicated that allelic variations in the SOD2 and GPX1 genes alter the distribution and relative concentrations of SOD2 and GPX1 in mitochondria, thereby affecting the dynamic between the production and elimination of H(2)O(2). Experimental and epidemiological evidence supporting a conflicting role of SOD2 in tumor biology, and epidemiological evidence that SOD2 and GPX1 can interact to affect cancer risk and progression indicated that it is the net accumulation of mitochondrial H(2)O(2) (mtH(2)O(2)) resulting from of the balance between the activities SOD2 and anti-oxidants such as GPX1 that determines whether SOD2 prevents or promotes oncogenesis. In this review, research supporting the idea that GPX1 is a gatekeeper restraining the oncogenic power of mitochondrial ROS generated by SOD2 is presented. This article is part of a Special Issue entitled Respiratory complex I, edited by Giuseppe Gasparre, Rodrigue Rossignol and Pierre Sonveaux.